Coupled rheo-physical effects of blended cementitious materials on wet packing and flow properties of inert suspensions. (15th February 2021) - Youness, Dima; Yahia, Ammar; Tagnit-Hamou, Arezki
Abstract: In addition to particle-liquid interaction, the flowability of blended-cementitious suspensions depends on the physical properties and packing of solid particles. The coupled physical effects of various single and blended cementitious materials on the flow behavior of inert suspensions was evaluated. General use cement (GU), ground-glass pozzolan, fly ash-F, blast furnace slag, limestone fillers, and their binary and ternary combinations were investigated. The blending effect on the wet packing and flowability of the investigated systems was highlighted. The overall dry flowability of the single powders and blended systems depends on the angles of repose (αF ) and spatula (αS ), which reflect their specific surface area. The dry physical parameters were in good agreement with their performance in suspension. The decrease of angles of repose and spatula resulted in higher maximum wet packing. All the investigated single powders showed higher relative alcohol demand and lower wet density than GU cement. The dry packing, morphology, and cohesion of blended cementitious materials influenced the minimum and relative liquid demand. Particles with higher aspect ratio and lower circularity increased the alcohol demand to initiate the flow of suspensions. Powders with higher angle values exhibited lower flowability. Good correlations were established to evaluate the coupled effects of different physical characteristics of powders on the wet packing of suspensions. Higher wet packing of single and blended systems having coarser average diameter values can be achieved by simultaneously reducing their compressibility and average diameter-to-fineness (d50 2 /SSA) ratio values.